Measurement of e + e − → ωη ′ cross sections at s = 2. 000 to 3. 080 GeV - Ablikim, M; Achasov, MN; Adlarson, P; Ai, XC; Aliberti, R; Amoroso, A; An, MR; An, Q; Bai, Y; Bakina, O; Balossino, I; Ban, Y; et al. (Springer, 2024)
We measured the Born cross sections for the process e+e− → ωη′ at 22 center-of-mass energies from 2.000 to 3.080 GeV with the BESIII detector at the BEPCII collider. We observed a resonant structure with a statistical significance of 9.6σ. A Breit-Wigner fit determines its mass to be MR = (2153 ± 30 ± 31) MeV/c2 and its width to be ΓR = (167 ± 77 ± 7) MeV, where the first uncertainties are statistical and the second are systematic.